Antinociceptive activity of methanolic extract of the leaves of Feronia limonia Linn (Bangladesh Journal of Physiology and Pharmacology, 2014)
The antinociceptive activity of the methanolic extract of the leaves of Feronia limonia Linn. (Family Rutaceae) was investigated using acetic acid-induced writhing model and tail flick test in swiss albino mice. The extract produced about 26.01% ( p< 0.01), 39.88% ( p< 0.01) and 57.07% (p< 0.01) writhing inhibition at the dose of 100, 200 and 400 mg/kg of body weight respectively, which was comparable to the standard drug diclofenac sodium where the inhibition was about 63.58% (p< 0.01) at the dose of 25 mg/kg of body weight. All doses of extracts significantly (p